Mengajar Bahasa Inggris Untuk Siswa Keterbelakangan di SMPLB PGRI Pamekasan - Fitrah Yuliawati; Ika Nuriyanti; Jaftiyatur Rohaniyah (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2021)
The research was aimed at delineating the practice of teaching English for Down Syndrome students in a special secondary school of in Pamekasan, East Java. In this qualitative research, the data were gathered from observation, interview and documentation. An EFL teacher teaching English to students with Down Syndrome participated in this research. The result showed that the teacher taught English through several stages including opening, materials presentation, evaluation and assessment, and closing. It was also revealed that using demonstration method and visual media can increase the students’ attention in learning English. It seemed that pictures are more preferred by the students in learning English, and thus it is recommended that teachers use more visual objects and realia in teaching English for Down Syndrome students as alternative way to improve the teaching quality.